"It's Not Broke, So Let's Not Try to Fix It": Why Patients Decline a Cardiovascular Implantable Electronic Device. Issue 10 (1st June 2014) - OTTENBERG, ABIGALE L.; MUELLER, PAUL S.; TOPAZIAN, RACHEL J.; KAUFMAN, SHARON; SWETZ, KEITH M.
<x xml:space="preserve">Abstract</x> Background Few patients decline therapy of a cardiovascular implantable electronic device (CIED), and little is known about the characteristics or reasoning of those who do. Our objective was to describe the reasons why patients decline CIED implantation using qualitative methods. Methods Qualitative, engaging thematic analysis. Three patient focus groups led by two trained facilitators and one semi‐structured interview guide. Results Of the 13 patients, two were women and all were white (median age [range], 65 [44–88] years). Five themes emerged: (1) don't mess with a good thing; (2) my health is good enough; (3) independent decision making; (4) it's your job, but it's my choice; and (5) gaps in learning. Most patients who decline CIEDs are asymptomatic. Other reasons to decline included feeling well, enjoying life, acceptance of the future, desire to try to improve health through diet and exercise, hearing of negative CIED experiences, and unwillingness to take on associated risks of CIED implantation. A medical record review showed that clinicians understand patients' reasons for declining CIED treatment. However, focus group data suggest that gaps in patients' knowledge around the purpose and function of CIEDs exist and patients may benefit from targeted education. Conclusions Patients decline implantation of CIEDs for various reasons. Most patients who decline therapy are asymptomatic at the time of their device consult. Focus group information show data suggestive that device consultations should be enhanced to address gaps in patient learning and confirm knowledge transfer. Clinicians should revisit treatment options iteratively.